Status and Prospects of the Accelerator Mass Spectrometry Center of the Institu te of Applied Physics of NASU - Moskalenko, V.B.; Danilchenko, S.N.; Drozdenko, A.A.; Storizhko, V.Yu.; Chivanov, V.D.; Chizhov, I.G. (Science and Innovation, 2024)
The paper deals with the issues related to development of the Accelerator Mass Spectrometry CF of IAP of NASU. The first archaeometrical results have been presented. The main tasks and directions of further CF development have been discussed.